Infrared and Visible Image Fusion with Overlapped Window Transformer - Liu, Xingwang; Mersha, Bemnet Wondimagegnehu; Hirota, Kaoru; Dai, Yaping (Journal of advanced computational intelligence and intelligent informatics, 2025)
An overlap window-based transformer is proposed for infrared and visible image fusion. A multi-head self-attention mechanism based on overlapping windows is designed. By introducing overlapping regions between windows, local features can interact across different windows, avoiding the discontinuity and information isolation issues caused by non-overlapping partitions. The proposed model is trained using an unsupervised loss function composed of three terms: pixel, gradient, and structural loss. With the end-to-end model and the unsupervised loss function, our method eliminates the need to manually design complex activity-level measurements and fusion strategies. Extensive experiments on the public TNO (grayscale) and RoadScene (RGB) datasets demonstrate that the proposed method achieves the expected long-distance dependency modeling capabilities when fusing infrared and visible images, as well as the positive results in both qualitative and quantitative evaluations.